Odpowiedzi

  • Użytkownik Zadane
2010-02-02T20:00:31+01:00
A) (-4x+8):4 = -x + 2
b) (5x+10y):5 = x + 2y
c) (6p2-8pr):(-2) = -3p² + 4pr
d) (3x-6xy+1):(-3) = -x + 2xy - 1/3
e) (x2+x-1):(-0.16) = (x² + x - 1) : (- 4/25) = (x² + x - 1) * (-25/4) = -25/4x² - 25/4x + 25/4 = -6 1/4x² - 6 1/4x + 6 1/4
f) (2.5x2-0.5x+1):5 = 0,5x² - x + 1/5
2 4 2
2010-02-02T20:03:57+01:00
Przekżtałć ilorazy na sumy.
a) (-4x+8):4 =
= (-4x) : 4 + 8 : 4 =
= -x + 2

b) (5x+10y):5=
= 5x : 5 + 10y :5=
= x + 2y

c) (6p2-8pr):(-2)=
= 6p² :(-2) - 8pr : (-2)=
= - 3p² + 4pr

d) (3x-6xy+1):(-3)=
= 3x:(-3) - 6xy : (-3) + 1 : (-3)=
= -x + 2xy -1/3

e) (x2+x-1):(-0.16)=
= x² : (-16/100) + x : (-16/100) -1 : (- 16/100)=
= x² *(-100/16) + x *(-100/16) - 1*(-100/16)=
= x²*(-25/4) + x ( -25/4) - 1*(-25/4) =
=( -25/4)x² - 25/4x + 25/4 =
= (-25/4)[ x² + x - 1)

f) (2.5x2-0.5x+1):5=
= (2,5x² :5 - 0,5x : 5 + 1 : 5=
= 0,5x² - 0,1x + 1/5=
= 0,5x² - 0,2 + 0,2

1 5 1